2020
DOI: 10.3389/fmars.2020.00216
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Niches and Biodiversity: A Test Case in the Deep Sea Benthos

Abstract: The great anthropogenic alterations occurring to carbon availability in the oceans necessitate an understanding of the energy requirements of species and how changes in energy availability may impact biodiversity. The deep-sea floor is characterized naturally by extremely low availability of chemical energy and is particularly vulnerable to changes in carbon flux from surface waters. Because the energetic requirements of organisms impact nearly every aspect of their ecology and evolution, we hypothesize that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 117 publications
(159 reference statements)
3
19
0
Order By: Relevance
“…At the same time, our analysis confirms the presence of distinct basal infaunal communities and a faunal separation between northern (Arctic) and southern (Atlantic) assemblages at a latitude that corresponds with the operational oceanographic [66] and benthic [56] polar front. By extension, when taken together, our findings give credence to the view that Arctic dwelling benthic assemblages are more robust than physiological assessments may indicate [100], and it is tempting to speculate that a proportion of the community are adapted to maximize seasonal shifts in, for example, resource availability [101]. However, as has been highlighted before [28], detection of the influence of environmental conditions on the structure and function of benthic communities requires an overview of how functionally relevant infaunal traits covary with changing abiotic and biotic circumstance [102], and how species interactions and ecological roles vary with context [103].…”
Section: Discussionsupporting
confidence: 62%
“…At the same time, our analysis confirms the presence of distinct basal infaunal communities and a faunal separation between northern (Arctic) and southern (Atlantic) assemblages at a latitude that corresponds with the operational oceanographic [66] and benthic [56] polar front. By extension, when taken together, our findings give credence to the view that Arctic dwelling benthic assemblages are more robust than physiological assessments may indicate [100], and it is tempting to speculate that a proportion of the community are adapted to maximize seasonal shifts in, for example, resource availability [101]. However, as has been highlighted before [28], detection of the influence of environmental conditions on the structure and function of benthic communities requires an overview of how functionally relevant infaunal traits covary with changing abiotic and biotic circumstance [102], and how species interactions and ecological roles vary with context [103].…”
Section: Discussionsupporting
confidence: 62%
“…Proposed biogeographic provinces (Watling et al 2013) for the deep sea have also incorporated spatial variation in POC flux. These patterns of biodiversity and biogeographic provinces reflect both the theoretical and empirical evidence that POC specificity is an important niche axis for deep-sea species (McClain et al 2012b(McClain et al , 2018(McClain et al , 2020. Here, I quantify habitat specificity as the standard deviation of POC flux following research that deep-sea bivalve niches specifically have been demonstrated to reflect POC flux (McClain et al 2012b(McClain et al , 2018.…”
Section: Methodsmentioning
confidence: 97%
“…The relatively low respiration rate, and thus low metabolic demand, of N. pernula may leave it preadapted to the lower-productivity waters of this area, which is influenced by the Alaska Coastal Current. This low metabolic demand may confer a physiological competitive advantage over other taxonomic groups with higher carbon requirements ( Burton et al , 2011 ; McClain et al , 2020 ). Therefore, we hypothesize that species with low metabolic rates, such as Astarte sp.…”
Section: Discussionmentioning
confidence: 99%